Update in Primary Immunodeficiencies - Leonardi, Lucia; Rivalta, Beatrice; Cancrini, Caterina; Chiappini, Elena; Cravidi, Claudio; Caffarelli, Carlo; Manti, Sara; Calvani, Mauro; Martelli, Alberto; Miraglia del Giudice, Michele; Duse, Marzia; Marseglia, Gian Luigi; et al. (Acta Biomedica Atenei Parmensis, 2020)
Primary immunodeficiencies (PIDs) are inherited disorders classically characterized by increased susceptibility to infections. Nevertheless, in the last two decades, genomic analysis (such as NGS) coupled with biochemical and cellular studies led to a more accurate definition for a growing number of novel genetic disorders associated with PIDs. This revealed new aspects of the immune system and its function and regulation within these diseases. In particular, it has been clarified that the clinical features of PIDs are much broader that originally thought and extend beyond an increased susceptibility to infections. More specifi- cally, immune dysregulation is very often described in novel characterized PIDs and can lead to multiple autoimmune diseases, lymphoproliferation and malignancies. If not promptly diagnosed, these could negatively impact patient’s prognosis. The aim of this review is to increase the awareness of recently discovered PIDs, characterized predominantly by immune dysregulation phenotypes. Findings highlighted in this review suggest screening for immunodeficiency in patients with lymphoproliferation or early onset/multiple autoimmune diseases. Prompt diagnosis would potentially allow most successful treatment and clinical outcome for patients with PIDs.